1944 Water Treaty Between Mexico and the United States: Present Situation and Future Potential - Anabel Sánchez (El Colegio de la Frontera Norte, A.C., 2006)
Historically and culturally, water has always been considered to be a critical issue in Mexico- USA agenda. Along the 3 140-km border between Mexico and the United States, there is intense competition over the adequate availability of water. Water uses in urban border areas have continued to increase exponentially due to steadily increasing levels of population growth. Rapid industrialisation and urbanisation have resulted in more intensive patterns of water consumption and use. Agricultural water demands continue to be high. Mexico and the United States have established institutions and agreements to manage and protect rivers in the border region. The Treaty between Mexico and the United States for the Utilisation of Waters of the Colorado and Tijuana Rivers and of the Rio Grande was signed in 1944. With the turn of the century, the growing urban centers along the Rio Grande (Rio Bravo), where the river becomes the international boundary, started increasingly to depend on groundwater. This situation was not specifically addressed in the 1944 Treaty, especially as groundwater use at that time was not so significant.